Unusual congenital polydactyly in mini-pigs from the breeding group of the Institute of Cytology and Genetics (Novosibirsk, Russia) - S. V. Nikitin; S. P. Knyazev; V. A. Trifonov; A. A. Proskuryakova; Yu. D. Shmidt; K. S. Shatokhin; V. I. Zaporozhets; D. S. Bashur; E. V. Korshunova; V. I. Ermolaev (Вавиловский журнал генетики и селекции, 2021)
The article describes a new phenomenon in the breeding group of mini-pigs at the Institute of Cytology and Genetics (ICG, Novosibirsk): polydactyly (extra digits), which is unusual because the additional digits are situated at the lateral surface of legs or at the lateral and medial ones. This anomaly was first found here in 2017 in adult animals intended for culling due to incorrect positioning of the legs caused by flexor tendon laxity and resulting in weight-bearing on the palmar surface of the proximal phalanges (“bear’s paw”). Therefore, the polydactyly of mini-pigs has a pronounced negative selection effect. A visual survey of the livestock was conducted, and a description of the detected anomaly was compiled. The polydactyly in mini-pigs is a stand-alone trait and is not part of any syndromes. Individuals with polydactyly may have extra digits either on pectoral or on pectoral and pelvic limbs. On thoracic limbs, there may be either one lateral digit or a lateral digit and a medially located rudimentary hooflet. On pelvic limbs, only lateral extra digits can occur. Anatomical and morphological analyses showed that the lateral extra digit is an anatomically complete (“mature”) structure, whereas the medial rudimentary digit consists of only a hooflet without other structures characteristic of normal digits. Cytological examination revealed no specific karyotypic features, except for Robertsonian translocation Rb 16;17 previously reported for the mini-pigs of the same livestock. Cytological findings indicated that the polydactyly and Robertsonian translocation are not linked genetically. Genealogical analysis and results of crosses are consistent with a working hypothesis of recessive inheritance of the trait. Overall, the study shows that this type of polydactyly is anatomically and morphologically unique and not typical of Sus scrofa. In this species, only polydactyly types with medial accessory toes have been described and are usually inherited as a dominant trait with incomplete penetrance. In our case, the results of test crosses indicate recessive inheritance of the trait with varying expression and incomplete penetrance, because of which poorly expressed phenotypes are not visually detectable.